The influence of sewage fat composition on rheological behavior of metal injection moulding - Mohd Amin, Azriszul (Trans Tech Publications Inc, 2014)
Influence of sewage ratio or Fat Oil Grease (FOG) on the feedstock rheological characteristic for optimal binder formulation in metal injection moulding is evaluated besides Polypropylene (PP) as a backbone binder. Powder loading of 62% of water atomised SS316L being used here to determine the possibility of the best binder formulation which could be optimised for optimal powder loading base on rheological characteristic analysis. Two binder formulations of PP to SF being selected here are 60/40, 50/50 and 40/60 accordingly with the powder loading of 62% each binder formulation. The analysis will be base on viscosity, shear rate, temperature, activation energy, flow behaviour index and moldability index. It is found that from rheological result views, binder with composition of 60/40 and 50/50 exhibit pseudoplastic behaviour or shear thinning where the viscosity decrease with increasing shear rate. For 40/60 binder ratio is not suitable since the behaviour of the flow indicates dilatants behaviour. After considering all the criteria in terms of flow behaviour index, activation energy, viscosity and mouldability index, binder with ratio of 60/40 is evolve as a good selections.